Elbow precision machining technology by abrasive flow based on direct Monte Carlo method - Li, Jun-ye; Zhu, Zhi-bao; Wang, Bin-yu; Zhang, Xin-ming; Wang, Fei; Zhao, Wei-hong; Xu, Cheng-yu (Journal of Central South University, 2020)
The investigation was carried out on the technical problems of finishing the inner surface of elbow parts and the action mechanism of particles in elbow precision machining by abrasive flow. This work was analyzed and researched by combining theory, numerical and experimental methods. The direct simulation Monte Carlo (DSMC) method and the finite element analysis method were combined to reveal the random collision of particles during the precision machining of abrasive flow. Under different inlet velocity, volume fraction and abrasive particle size, the dynamic pressure and turbulence flow energy of abrasive flow in elbow were analyzed, and the machining mechanism of particles on the wall and the influence of different machining parameters on the precision machining quality of abrasive flow were obtained. The test results show the order of the influence of different parameters on the quality of abrasive flow precision machining and establish the optimal process parameters. The results of the surface morphology before and after the precision machining of the inner surface of the elbow are discussed, and the surface roughness R a value is reduced from 1.125 µm to 0.295 µm after the precision machining of the abrasive flow. The application of DSMC method provides special insights for the development of abrasive flow technology.